Digital Transformation and Banking sector workforce: An evaluation Study (International Journal of Scientific Research and Management (IJSRM), 2022)
The robust changes in banking sector in kind of Omni channel services and digital transformation has drastically changes in employees’ engagement with workforce and it affects each external and internal environment by redesigning internal processes and existing technique. Currently Banking system living within the era of customer choice because the traditional banking is dead ,in this case the difficult task for the banking is to allows the failties to folks and face the digital capabilities. There are many reasons that digital transformation takes place, such as servicing remote areas without physical branches, differentiation from competitors or reduction of operating costs. In any case, there are a lot of doubts about the acceptance of digital technologies and maintain a healthy employees’ engagement in banking sector .Thus ,this article examines digital transformation practices and evaluating the impact of digital transformation on banking sector workforce.The study involves public sector bank employees and a randomly selected 35 employees from public sector banks (State Bank of India and Canara Bank )in Davangere District ,shows that the effect of digital transformation on their workforce is found that through the descriptive statistics and pearson correlation, hence its proved that there is a sigficant relationship between the variables mentioned below and there is workforce and stress attached with digital transformation in Indian banking sector.